Persidangan di Hadapan Pilatus Pilatus dan Orang-Orang Yahudi dalam Yoh 18:28-19:6b - Riyadi, St. Eko (Jurnal Orientasi Baru, 2008)
Jesus was sentenced to death by Pontius Pilate. Although he found no guilt in Jesus, he decided to give Jesus over to the Jewish leaders who sought his death. Pilate, a Roman Judge, has thrown away the truth he believed and sentenced Jesus. On the other hand, the Jewish leader has thrown away their deepest conviction that God alone is their only King! They made themselves sons of Caesar, slaves of a Roman Imperator. Who is the winner in the trial before Pilate? It is not Pilate, nor the Jewish leaders. It is Jesus who keeps his strong conviction that God alone has power over him. He is God's Son, King of the Jews.